High‐Performance Delivery of a CRISPR Interference System via Lipid‐Polymer Hybrid Nanoparticles Combined with Ultrasound‐Mediated Microbubble Destruction for Tumor‐Specific Gene Repression. Issue 10 (15th January 2023) - Li, Yan; Wu, Pengying; Zhu, Mingting; Liang, Meiling; Zhang, Lei; Zong, Yujin; Wan, Mingxi
Abstract: The dCas9‐based CRISPR interference (CRISPRi) system efficiently silences genes without causing detectable off‐target activity, thus showing great potential for the treatment of cancer at the transcriptional level. However, due to the large size of the commonly used CRISPRi system, effective delivery of the system has been a challenge that hinders its application in the clinic. Herein, a combination of pH‐responsive lipid‐polymer hybrid nanoparticles (PLPNs) and ultrasound‐mediated microbubble destruction (UMMD) is used for the delivery of the CRISPRi system. The core–shell structure of PLPNs can effectively be loaded with the CRISPRi plasmid, and increases the time spent in the circulating in vivo, and "actively target" cancer cells. Moreover, the combination of PLPNs with UMMD achieves a higher cellular uptake of the CRISPRi plasmid in vitro and retention in vivo. Furthermore, when PLPNs loaded with a CRISPRi plasmid that targets microRNA‐10b (miR‐10b) are used in combination with UMMD, it results in the effective repression of miR‐10b in breast cancer, simultaneous disturbance of multiple cell migration and invasion‐related signaling pathways, and a significant inhibition of lung metastasis. Thus, the established system presents a versatile, highly efficient, and safe strategy for delivery of the CRISPRi system both in vitro and in vivo. Abstract : In this study, a strategy involving the combination of pH‐responsive lipid‐polymer hybrid nanoparticles and ultrasound‐mediated microbubble destruction is reported to overcome multiple barriers associated with the delivery of CRISPRi‐based gene repression system, the findings provide a versatile method that can be used for delivering the CRISPRi system with high efficiency and safety.